2007
DOI: 10.1590/s0100-879x2007000300010
|View full text |Cite
|
Sign up to set email alerts
|

Antimicrobial activity of the essential oil from Lippia sidoides, carvacrol and thymol against oral pathogens

Abstract: Dental caries and periodontal disease are associated with oral pathogens. Several plant derivatives have been evaluated with respect to their antimicrobial effects against such pathogenic microorganisms. Lippia sidoides Cham (Verbenaceae), popularly known as "Alecrimpimenta" is a typical shrub commonly found in the Northeast of Brazil. Many plant species belonging to the genus Lippia yield very fragrant essential oils of potential economic value which are used by the industry for the commercial production of p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
226
4
28

Year Published

2011
2011
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 349 publications
(267 citation statements)
references
References 25 publications
9
226
4
28
Order By: Relevance
“…However, only the first authors not found the presence of carvacrol. Following Botelho et al (2007), who studied the microbial activity of the same essential oil, they found that the major constituents among others were thymol (56.70%) and carvacrol (16.70%), wich diverges with the results reported in this research, mainly the percentage of content.…”
Section: Discussioncontrasting
confidence: 79%
See 1 more Smart Citation
“…However, only the first authors not found the presence of carvacrol. Following Botelho et al (2007), who studied the microbial activity of the same essential oil, they found that the major constituents among others were thymol (56.70%) and carvacrol (16.70%), wich diverges with the results reported in this research, mainly the percentage of content.…”
Section: Discussioncontrasting
confidence: 79%
“…and Candida albicans (BOTELHO et al, 2007). Essential oils as well as several terpenes have been utilized in agriculture against fungi, bacteria, nematodes and pest insects.…”
Section: Introductionmentioning
confidence: 99%
“…Currently, the use of natural products in the prevention and treatment of oral diseases has been increasing in rural and urban areas 10 . Among the numerous plants with therapeutic potential, Aloe Barbadensis Miller -commonly known as Aloe vera -, has been used as phytotherapeutic agent because of its antimicrobial, anti-inflammatory, antioxidants and healing properties 11 .…”
Section: Effects Of Fluoride and Aloe Vera Tooh Gel In Artificial Whimentioning
confidence: 99%
“…Todas as fenofases apresentaram altos índices de sincronia, com destaque para a frutificação e queda de folhas (Tabela 1), sendo esse um fator que, de acordo com Caldeira Júnior et al (2008), facilita o manejo da espécie no campo, já que a maioria das plantas apresentará a mesma fase fenológica, em determinado período.…”
Section: Resultado E Discussãounclassified
“…O potencial medicinal da espécie pode ser comprovado pela intensa atividade antimicrobiana apresentada pelo óleo essencial, como bem demonstram os trabalhos de Lemos et al (1990), Fontenelle, (2005, Oliveira et al (2006) e Botelho et al (2007). Este óleo essencial possui ainda atividade moluscicida contra o caramujo Biomphalaria glabra, e larvicida contra o estágio aquático do mosquito da dengue, Aedes aegyptii (Lorenzi & Matos, 2002;Cavalcanti et al, 2004).…”
Section: Introductionunclassified